Better Speed Better Comprehension: Introducing “Integrated Reading Comprehension Strategy - ABDULRAHMAN, NISHAD CHATHAMKULAM (2018)
Reading skills are assessed in many standardized English language proficiency tests, such as IELTS, TOEFL, FCE, CAE and CPE. Therefore, test-takers are required to employ effective strategies to perform well in the reading components of these tests. Taking this into account, this study introduces ‘Integrated Reading Comprehension Strategy’ (IRCS) and examines its effectiveness on participants’ reading comprehension, reading speed and reading test-anxiety. The study adopts a non-equivalent quasi-experimental embedded mixed-methods design and uses a sample of 30 teachers selected through convenience sampling from a private Indian school in Ajman, UAE. These participants are divided into two almost equal groups (experimental & control). Both quantitative and qualitative data are collected by means of pre and post-reading comprehension tests, pre and post-reading test-anxiety surveys and semi-structured post-production interviews. After three weeks of intervention, the quantitative data are analyzed using descriptive (frequency count, percentage & effect size) as well as inferential (independent & paired samples t tests) statistics, whereas content analysis is used for the purpose of analyzing the qualitative data. The findings of the study indicate that IRCS has no statistically significant effects on participants’ reading comprehension and reading speed although all the participants interviewed agree that IRCS enable them to read better and faster. On the other hand, the results of both quantitative and qualitative analyses reveal that IRCS plays a significant role in reducing participants’ reading test-anxiety levels. The study thoroughly discusses these findings, expounds its limitations, and offers suggestions for teachers, course material writers and future researchers.